GRAFIS LINGKUNGAN SEBAGAI MEDIA INFORMASI KOMUNIKASI VISUAL LUAR RUANG - Y. Andri Hervian Yunanto (Institut Seni Indonesia Yogyakarta, 2013)
Graphic environment is to make communication with people who visit or be somewhere.Directional information is a form of product creation graphic designer. Construction of something isbound to impact on environmental change as well as the development of sign systems. In fact so muchchaos that emerged as a result. Sameness and conformity to the building does not guarantee harmonywith the environment. Having regard to the natural environment, human needs, and the environment thatis built up is expected to create a harmonious environment.Keywords: Graphic environment, Sign systems, Harmonious